"Know the Signs" Suicide Prevention Media Campaign Is Aligned with Best Practices and Highly Regarded by Experts - Acosta, Joie D. (RAND Corporation, 2014)
Reports the findings of an evaluation by a panel of experts on the extent to which a suicide prevention media campaign in California is aligned with best practices in the field.